Youth Expectations and Perceptions of Generative Artificial Intelligence in Higher Education. - Cotino Arbelo, Andrea E.; González González, Carina S.; Molina Gil, Jezabel (International Journal of Interactive Multimedia and Artificial Intelligence, 2025)
Artificial Intelligence (AI) is not a recent innovation, what’s new is how accessible its features have become across multiple devices, apps, and services. Sensationalistic news can distort public perception by exaggerating AI’s capabilities and risks. This leads to misconceptions and unrealistic expectations, causing misunderstandings about the true nature and limitation of these tools. Such distortions can undermine trust and hinder the effective adoption and integration of AI into society. This study aims to address this issue by exploring the expectations and perceptions of young individuals regarding Generative Artificial Intelligence (GAI) tools. It explores their understanding of GAI and related devices, such as virtual assistants, chatbots, and social robots, which can incorporate GAI. A total of N=100 university students engaged in this study by completing a digital questionnaire distributed through the virtual campus of the University of La Laguna. The quantitative analysis uncovered a significant gap in participants’ understanding of GAI terminology and its underlying mechanisms. Additionally, it shed light on a noteworthy gender based discrepancy in the expressed concerns. Participants commonly recognized their ability to communicate effectively with GAI, asserting that such interactions enhance their emotional well-being. Notably, virtual assistants and chatbots were perceived as more valuable tools compared to social robots within the educational realm.